2021
DOI: 10.1177/15563316211010720
|View full text |Cite
|
Sign up to set email alerts
|

Use of Implant-Mediated Guided Growth With Tension Band Plate in Skeletally Immature Patients With Knee Pathology: A Retrospective Review

Abstract: Background: Skeletally immature patients with coronal plane angular deformity (CPAD) may be at increased risk for intra-articular pathology and patellofemoral instability (PFI). These patients may be candidates for implant-mediated guided growth (IMGG) procedures with tension band plates to address CPAD in addition to procedures for concomitant knee pathology. However, there are limited data on performing these procedures simultaneously. Questions/Purpose: We sought to demonstrate the feasibility of combined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…They similarly noted the resolution of PFI in all but one patient who required revision MPFL reconstruction 5 months after index surgery [30]. Ellsworth et al reported correction of genu valgum from 18.8° to 2.7° postoperatively in their patients with PFI, though their outcome data were presented in aggregate amongst all patients with coronal plane angular deformity with various knee pathologies [10]. Tomasevich et al performed simultaneous MPFL repair in addition to guided growth, noting that 36% required subsequent procedures for recurrent PFI [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They similarly noted the resolution of PFI in all but one patient who required revision MPFL reconstruction 5 months after index surgery [30]. Ellsworth et al reported correction of genu valgum from 18.8° to 2.7° postoperatively in their patients with PFI, though their outcome data were presented in aggregate amongst all patients with coronal plane angular deformity with various knee pathologies [10]. Tomasevich et al performed simultaneous MPFL repair in addition to guided growth, noting that 36% required subsequent procedures for recurrent PFI [40].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative deformity recurrence is one common concern following hardware removal after guided growth procedures [7]. This phenomenon may occur due to increased growth at the hemiepiphysis after implant removal compared with the contralateral hemiepiphysis, particularly in younger patients with residual growth potential at the time of implant removal [10, 18]. Two extremities in our series experienced a growth‐related complication prior to hardware removal, with both extremities developing significant overcorrection (HKA > 5°).…”
Section: Discussionmentioning
confidence: 99%
“…A statistical analysis was performed by calculating the average for each group and then performing a one-way ANOVA test. Because we had a limited number of each implant to use for testing (5), no sample size calculation was performed. This study only involved biomechanical testing of the listed implants, so no institutional review board approval was necessary.…”
Section: Methodsmentioning
confidence: 99%
“…G uided growth is a surgical technique commonly used to correct angular deformity in skeletally immature patients. [1][2][3][4][5] Various guided growth plate constructs have been utilized in clinical practice. [6][7][8][9][10][11] The standard two-hole guided growth plate is most commonly used but other versions are commercially available including four-hole guided growth plates and two hole guided growth plates with locking screws.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation